Pembinaan Ekstrakurikuler Sepakbola Di (Ite) College East Singapore (Universitas Negeri Semarang, 2021)
Institute of Technical Education College East Singapore is one of the schools in Singapore that is equivalent to vocational school in Indonesia. Institute of Technical Education College East Singapore has 28 Co- Curricullar Activities (CCA) or commonly called extracurricular. All students are required to choose 1 extracurricular according to their talents and interests. Extracurricular football is one of the extracurricular that has many fans and one of the sports that contributes excellent achievements. The result of good achievement is certainly a good coaching result that was carried out at Ite College East Singapore. But behind it all must be the role of management to help in achieving such good achievements. This pioneered researchers to find out how management at Co- Curricullar Activities (CCA) football is viewed from management functions namely planning, organizing, leadership, and supervision. This research approach uses descriptive qualitative. The research was conducted at PE Departement Ite Collegge East Singapore. The subjects of this study were managers, extracurricular coaches, and students. Data collection techniques using observation, interviews, and documentation. Data analysis uses data collection, data reduction, data presentation, and inference.The results of research on Football Extracurricular Coaching Management in Ite Collegge East Singapore from the theory of management functions obtained that the overall Planning function has been running well in accordance with the material, but there are some shortcomings that need to be improved from the sub indicators of the training program, and improvements to the funding sub indicators. The organizing function is already well underway, a structorized organizational structure, clear organizational objectives, proper member placement, good environmental support, and good coordination. The leadership function of the implementation of the training program has been running well. Coaches and administrators have also taken a social approach to motivate students to be active and excel. The communication between managers, coaches, and athletes is very good. The supervisory function of the achievements achieved by the Co- Curricullar Activities (CCA) of football has been good and students are experiencing good development as well. Institute of Technical Education College East Singapore is one of the schools in Singapore that is equivalent to vocational school in Indonesia. Institute of Technical Education College East Singapore has 28 Co- Curricullar Activities (CCA) or commonly called extracurricular. All students are required to choose 1 extracurricular according to their talents and interests. Extracurricular football is one of the extracurricular that has many fans and one of the sports that contributes excellent achievements. The result of good achievement is certainly a good coaching result that was carried out at Ite College East Singapore. But behind it all must be the role of management to help in achieving such good achievements. This pioneered researchers to find out how management at Co- Curricullar Activities (CCA) football is viewed from management functions namely planning, organizing, leadership, and supervision. This research approach uses descriptive qualitative. The research was conducted at PE Departement Ite Collegge East Singapore. The subjects of this study were managers, extracurricular coaches, and students. Data collection techniques using observation, interviews, and documentation. Data analysis uses data collection, data reduction, data presentation, and inference.The results of research on Football Extracurricular Coaching Management in Ite Collegge East Singapore from the theory of management functions obtained that the overall Planning function has been running well in accordance with the material, but there are some shortcomings that need to be improved from the sub indicators of the training program, and improvements to the funding sub indicators. The organizing function is already well underway, a structorized organizational structure, clear organizational objectives, proper member placement, good environmental support, and good coordination. The leadership function of the implementation of the training program has been running well. Coaches and administrators have also taken a social approach to motivate students to be active and excel. The communication between managers, coaches, and athletes is very good. The supervisory function of the achievements achieved by the Co- Curricullar Activities (CCA) of football has been good and students are experiencing good development as well.